Role of Ranolazine in cardiovascular disease and diabetes: Exploring beyond angina. (15th January 2017) - Banerjee, Kinjal; Ghosh, Raktim Kumar; Kamatam, Sravani; Banerjee, Arnab; Gupta, Anjan
Abstract: Ranolazine was FDA approved for chronic angina in 2006. Since then, there has been extensive research involving this drug. The mechanism of action, debatable at the time of approval, has been demonstrated. Ranolazine acts via inhibition of late sodium channel current in the myocardium. This acts by lowering abnormally high cytosolic calcium levels. Other possible clinical applications of Ranolazine have also been explored. Out of many lines of investigation, its effects in atrial fibrillation, especially post-CABG and recurrent atrial fibrillation show promise. It has also shown definite HbA1c lowering effects when used in diabetics with coronary artery disease. Other possible indications for the drug include pulmonary arterial hypertension, diastolic dysfunction and chemotherapy-induced cardiotoxicity. This review aims to summarize major research regarding Ranolazine in potential applications beyond chronic angina. There are few dedicated large, randomized, phase III trials exploring the newer effects of Ranolazine. There are a few such trials underway, but more are needed. Highlights: Mechanism of action of Ranolazine: blockage of late sodium currents in myocardial cells FDA approved indication: chronic angina Promising new data: atrial fibrillation, diastolic dysfunction, diabetes with angina Further avenues of investigation: post-PCI, chemotherapy induced cardiotoxicity